Frontostriatal grey matter atrophy in amyotrophic lateral sclerosis A visual rating study - Radakovic,Ratko (2018)
ABSTRACT Amyotrophic lateral sclerosis (ALS) is characterised by frontostriatal grey matter changes similar to those in frontotemporal dementia (FTD). However, these changes are usually detected at a group level, and simple visual magnetic resonance imaging (MRI) cortical atrophy scales may further elucidate frontostriatal changes in ALS. Objective: To investigate whether frontostriatal changes are detectable using simple visual MRI atrophy rating scales applied at an individual patient level in ALS. Methods: 21 ALS patients and 17 controls were recruited and underwent an MRI scan. Prefrontal cortex sub-regions of the medial orbitofrontal cortex (MOFC), lateral orbitofrontal cortex (LOFC) and anterior cingulate cortex (ACC), striatal sub-regions of the caudate nucleus (CN) and nucleus accumbens (NAcc) were rated using visual grey matter atrophy 5-point Likert scales. Results: Significantly higher atrophy ratings in the bilateral MOFC only in ALS patients versus controls was observed (p<.05). Patients with greater MOFC atrophy had significantly higher atrophy of the CN (p<.05) and LOFC (p<.05). Conclusion: Use of simple visual atrophy rating scales on an individual level reliably detects frontostriatal deficits specific to ALS, showing MOFC atrophy differences with associated CN and LOFC atrophy. This is an applicable method that could be used to support clinical diagnosis and management.